PENGARUH LEVEL DAN CARA PEMBERIAN MADU TERHADAP KONSUMSI PAKAN DAN PERTUMBUHAN PUYUH JANTAN (COTURNIX-COTURNIX JAPONICA) - Khoirudin, Nandiwahib Mualim; Ismoyowati, Ismoyowati; Tugiyanti, Elly (ANGON: Journal of Animal Science and Technology, 2022)
Background. This study aimed to examine the effect of levels and methods of giving honey on the feed consumption and growth of male quail. The study was conducted from December 4, 2020, to January 15, 2021, at Ketapang Farm, Sokaraja Kulon. Materials and methods. The material of this study used were 100 male quails age three weeks which was maintained for six weeks. The material used as a treatment is randu honey. The study was conducted using the experimental method and Completely Randomized Design (CRD). There were five treatments, repeated for times, each unit containing 5 reads. The treatment tested were R₀: without treatment (control); R₁P₁: feed ration and 2,5 ml honey; R₁P₂: feed ration and 5 ml honey; R₂M₁: drinking water and 2,5 ml honey; R₂M₂: drinking water and 5 ml honey. The variable that is recorded an observed, which includes feed consumption and growth. The analysis of variance showed that the use of giving honey through feed and drinking water had no significant effect (P>0,05) on feed consumption and growth. Results. The average result of content feed consumption of male quail consecutive was R₀: 18,39 ± 1,09 gram/day; R₁P₁: 18,17 ± 1,04 gram/day; R₁P₂: 17,68 ± 1,89 gram/day; R₂M₁: 18,23 ± 0,52 gram/day; R₂M₂: 16,81 ± 1,35 gram/day. The average result of growth of male quail consecutive was R₀: 2,1 ± 1,3 gram/day; R₁P₁: 2,23 ± 1,58 gram/day; R₁P₂: 2,07 ± 1,93 gram/day; R₂M₁: 2,04 ± 2,47 gram/day; R₂M₂: 1,97 ± 2,30 gram/day. Conclusion. This research can conclude that giving honey 0 ml, 2.5 ml, and 5 ml through feed and drinking water has not been able to decrease the consumption and has not been able to increase the growth of the male quail.